أساليب المعاملة الوالدية و علاقتها بمستوى الطموح لدى عينة من تلاميذ السنة الرابعة متوسط - خديجة موافق; بوضلعة وهيبة; بيقع صليحة (My University, 2018)
The present study aimed at examining the correlation between parental treatment methods and the level of ambition in a sample of middle school students in the city of Laghouat- Mijahid Gilali Senousi, as well as knowledge of gender differences in parental treatment and level of ambition and knowledge of differences in parental treatment methods according to the educational level of parents Father and mother, and knowledge of the differences in the level of ambition according to the retake of a year (retaker, non-taker).  Our study has determined the descriptive approach that we saw fit and appropriate for this study, while the sample of the study consisted of 80 students in 4th year of middle school. In order to achieve the objectives of the study, to test hypotheses we used the measure of parental treatment (Schafer) and the scale of aspiration (Camelia Abdel Fattah). The results of the study revealed the following:  The existence of a correlation between the methods of parental treatment and the level of ambition among the pupils of the middle school of Laghouat.  There were statistically significant differences in the methods of parental treatment in a sample of middle school students due to gender variable.  There were statistically significant differences in the level of ambition among a sample of middle school students due to the research.  There are no statistically significant differences in the methods of parental treatment according to the educational level of the father (no studies, primary, intermediate, secondary, university).  There are no statistically significant differences in the methods of parental treatment according to the educational level of the mother (no studies, primary, intermediate, secondary, university).  There were no statistically significant differences in the level of ambition among a sample of students of the intermediate stage due to the retaking of a year (retakers, non-takers)